Birth Size and Gestational Age Specific Outcomes of Inhaled Nitric Oxide Therapy in Preterm Neonates with Clinically Diagnosed Pulmonary Hypertension - Udland, Carley J.; Carey, William A.; Weaver, Amy L.; Mara, Kristin C.; Clark, Reese H.; Ellsworth, Kevin R. (American Journal of Perinatology, 2019)
Objective Among neonates of 22 to 29 weeks' gestational age (GA) who required mechanical ventilation for the treatment of respiratory distress syndrome (RDS) and clinically diagnosed pulmonary hypertension (PH), we tested our hypothesis that the association between early treatment with inhaled nitric oxide (iNO) and survival would vary according to birth size and GA.Study Design Because iNO was not randomly prescribed to patients in this cohort, we used propensity score matching to pair a neonate who received iNO at a chronological age of ≤7 days with an unexposed neonate with similar baseline characteristics. The primary outcome was inhospital mortality, which we evaluated based on size for GA and GA strata using the Cox proportional hazards regression model.Results Among 1,531 neonates who met study criteria, we created a propensity score matched cohort of 615 pairs of neonates (iNO-exposed and unexposed). The risk of inhospital mortality for iNO-exposed neonates was observed only in the minority (<10%) who were large for GA, though this finding did not persist when matching for illness severity.Conclusion Early treatment with iNO is not associated with survival in most extremely premature neonates with RDS and clinically diagnosed PH when stratified for birth size or GA.
Keywords: inhaled nitric oxide; neonate; prematurity; pulmonary hypertension; respiratory distress syndrome